2017
DOI: 10.1002/ags3.12003
|View full text |Cite
|
Sign up to set email alerts
|

Intersphincteric resection for very low rectal cancer: A review of the updated literature

Abstract: Intersphincteric resection (ISR) has rapidly increased worldwide including laparoscopic surgery. However, there are some concerns for the definition of ISR, surgical technique, oncological outcome, anal function, and quality of life (QoL). The aim of the present study is to evaluate those issues. A review of this surgical technique was carried out by searching English language literature of the PubMed online database and appropriate articles were identified. With regard to open‐ISR, the morbidity rate ranged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 82 publications
(199 reference statements)
1
49
1
2
Order By: Relevance
“…After transection of the inferior mesenteric artery and vein, total mesorectal excision (TME) was carried out as a standard surgical procedure, and bilateral LLND was done when the depth was T3 or deeper, as a rule . To secure a 2‐cm resection margin, ISR was selected for tumors located within 2 cm from the upper margin of the levator ani muscle attachment region . For anastomosis in LAR and ISR, double‐stapled and hand‐sewn coloanal anastomosis were carried out, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…After transection of the inferior mesenteric artery and vein, total mesorectal excision (TME) was carried out as a standard surgical procedure, and bilateral LLND was done when the depth was T3 or deeper, as a rule . To secure a 2‐cm resection margin, ISR was selected for tumors located within 2 cm from the upper margin of the levator ani muscle attachment region . For anastomosis in LAR and ISR, double‐stapled and hand‐sewn coloanal anastomosis were carried out, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Studies comparing open and laparoscopic ISR have reported long-term survival data with 5-year OS, DFS and LR rates ranging from 62% to 97%, 66.7% to 87% and 0 to 23%, respectively. 56,57,58,59,60,61,62,63,64 A recent review by Shirouzu et al 3 on a total of 22 studies evaluated oncological outcomes after ISR for both open and laparoscopic approaches. The results showed a radical resection (R0 resection) in over 90% of patients, but there was wide variation in the reported resection margins: the DRM was between 5 and 25 mm, and the CRM was ≤1 mm in 4% to 19.6% of cases.…”
Section: Oncological Outcomes With Robotic Isdmentioning
confidence: 99%
“…The main concern for ISR is local recurrence in the pelvic cavity (including at the anastomotic site), which is reported to be between 0 and 22.7%. 3 Neoadjuvant CRT is used to both down-size the tumor and down-stage the disease and is a standard strategy to avoid positive CRM and reduce LR in locally advanced rectal cancer as per the NCCN guidelines. 65,66,67 However, in Japan, neoadjuvant CRT is not carried out for resectable cT1-3 tumors, regardless of the presence of lymph node metastasis within the TME 3 , with Akagi et al 68 reporting a low rate of LR (4.8%).…”
Section: Oncological Outcomes With Robotic Isdmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is much concern about the functional outcome such as anal function and quality-of-life (QoL). They seem to deteriorate the more distal there section is performed, with signifi can differences between the conventional laparoscopic and the open approach [5]. Innovations in the transanal approach like TaTME claim to have a more nerve-preserving and nerve-oriented focus due to a better overview, but long-term data are still not yet available.…”
mentioning
confidence: 99%